Deregulation and Competition in the Financial Industry - Barron, D; West, E; Hannan, M (1998)
Deregulation has stimulated much economic and political interest. This paper develops a framework for understanding the effects of deregulation from an ecological perspective and reports empirical studies of financial institutions (banks, thrifts and mutual funds) at two levels of analysis: the system and the population. These both show that deregulation bad a dramatic impact on the level of competitive intensity within the financial industry. The main contributions of this paper are the application of a general sociological theory of organizational dynamics to understanding deregulation and the development of a general approach to modelling which could lead to new ways to evaluate the organizational consequences of major environmental changes.